First person - Melanie Gartz (The Company of Biologists, 2020)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Melanie Gartz is first author on 'Duchenne muscular dystrophy (DMD) cardiomyocyte-secreted exosomes promote the pathogenesis of DMD-associated cardiomyopathy', published in DMM. Melanie conducted the research described in this article while a graduate student in Jennifer Strande's lab at the Medical College of Wisconsin, Cardiovascular Research Center, Milwaukee, WI, USA. She is now a postdoctoral fellow in the lab of Michael Lawlor at the Medical College of Wisconsin, Neuroscience Research Center, investigating the molecular mechanisms that underlie cardiomyopathy in Duchenne muscular dystrophy.